Um projeto de extensão: diálogos sobre empoderamento de mulheres rurais em estudo de caso do grupo Quitandas de Ouros no município de Conceição dos Ouros em Minas Gerais - Souza, Lívia Santos Lemos de (2019)
The historical trajectory of public universities in Brazil, runs through various approaches and actions, leading to a diversity of definitions about the concept of University Extension, perceived as a concept in permanent construction. However, situations and practices that reveal new directions require advances and directions for a more stable definition. The 80's was marked by the creation of the 1st National Forum of Pro-Dean of Extension of the Brazilian Public Universities, aiming to build the concept and Institutionalization of Extension. In the last decade, this discussion was focused on strengthening the concept of extension, regulating the partnership between university and society, giving Higher Education Institutions (IES) a great responsibility. In this direction, the intention of the Public University is to accomplish the interface among three pillars of the Brazilian Public University (teaching-research and extension), through the National Policy of University Extension (PNEU) in accordance with FORPROEX. This document reaffirms the objectives elaborated throughout the history of the Forums, in addition to presenting the guidelines that conduct the extension actions. On the other hand, the Federal Institutes of Education, Science and Technology have adopted the concept of technological extension, based on the concept of university extension, but it not only links teaching and research activities to the demands of the region, but also seeks to associate extension to the demands of the community that surrounds the institution's campuses. In order to promote technological extension, the Secretariat of Professional Education of the Ministry of Education (SETEC), through the opening of calls for proposals, has supported in the last years the development of some projects with this specificity.On that occasion, in 2014, public servants of IFSULDEMINAS, in partnership with EMATER/MG, approved the project entitled "Development of cassava products for insertion in school feeding as a perspective of food security and empowerment of rural women in Conceição dos Ouros ", through the call for proposals CNPq-SETEC/MEC Nº017/2014.The project aimed at the development of viable food products (quitandas), from a nutritional and economic point of view, for marketing in school feeding, with a focus on the inclusion of rural women in the job market.Participants were rural women who, after joining the project, were entitled: "Quitandas de Ouro Group”. Faced with these factors, the research titled: “An Extension Project: dialogues on the empowerment of rural women in a case study from the Quitandas de Ouro Group in the Municipality of Conceição dos Ouros in Minas Gerais”.The research was carried out with five women from the Quitandas de Ouro Group and sought to understand the impacts of the extension project on the women group. The research aims to know the contributions, limits and challenges of the extension project, from the perspective of the empowerment and income generation of the women from the Quitandas de Ouro Group, as well as to identify these factors with regard to the guidelines of the National Policy of University Extension.